ТУПРОҚ УНУМДОРЛИГИНИ БАҲОЛАШНИНГ АЙРИМ ЖИҲАТЛАРИ (Scientific journal of the Fergana State University, 2023)
In the article, it is shown that soil  is a complex object to evaluate its fruitfullness, as well as  analyzed different methods in this sphere. It emphasises the  integrity of the  usage of models of soil on evaluating  of  its fertility,  the soil has its characteristics and peculatities and its formation of fruitfulness are conditioned  by definite conditions.